PS48 Processes Of Change: What Are The Specific Pathways And Project Components That Have A Positive Impact On The Well-Being Of Participants In A 'Well London' Project?. (17th September 2012) - Derges, J; Draper, A; Clow, A; Lynch, R; Jain, S
Abstract : Background: This paper presents follow-up data from a qualitative study of a Big Lottery funded 'Well London' project; an initiative set up to improve the health and well-being of Londoners living in areas historically marked by social, economic and environmental deprivation. The project introduced a series of health interventions: healthy eating, physical activity, and mental health and well-being, across a total of 20 areas within London. An evaluation of the interventions was conducted through a series of in depth semi-structured interviews with residents in 3 of the areas. Participants were interviewed twice: initially at the start of the interventions and again twelve months later. The interviews explored which of the project components acted positively on participant's sense of well-being and lead to changes in health behaviour. The methodology used, placed emphasis on the opinions and reflections of study participants and responds to Popay's call for research to be centred not only on theoretical concerns, but also to be attentive to 'lay' theories of health. Methods: Two sets of 60 semi-structured interviews, taking place a year apart were conducted across three locations identified as Census Lower Super Output Areas (LSOAs). These measured changes in health behaviour and residents' perceptions of 'well-being' that arose following the Well London interventions. Residents were interviewed about their experiences and perceptions of the neighbourhood; also their health and views of the Well London interventions. Residents who had not taken part in the project interventions were also selected and interviewed, for comparison. Results: The study found that the project objectives succeeded where there were at least one of the following present; a) high levels of individual motivation; b) the involvement of external agencies in the form of key worker and/or agency support; c) where residents were involved in the organisation and dissemination of the projects, often as volunteers; and d) where the environment was made accessible, safe and conducive to a sense of belonging and 'community ownership'. Conclusion: The findings indicate that the Well London project increased perceptions of well-being in populations defined by inner city social disadvantage. However, the pathways to change are complex and not easily generalized. Success is dependent on multiple interacting interpersonal, social and contextual factors, as well as the actual type of interventions themselves.